2019
DOI: 10.1111/den.13448
|View full text |Cite
|
Sign up to set email alerts
|

Combined side‐by‐side and stent‐in‐stent method for triple metal stenting in patients with malignant hilar biliary obstruction

Abstract: Background and Aim Endoscopic placement of three branched self‐expandable metallic stents (SEMS) for high‐grade malignant hilar biliary obstruction (MHBO) is technically challenging. We examined the feasibility and efficacy of a novel stenting method combining side‐by‐side and stent‐in‐stent (SBSIS) placement for MHBO. Methods Between January 2015 and December 2018, 27 consecutive patients with high‐grade MHBO underwent SBSIS placement. We evaluated the technical success, functional success, recurrent biliary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Also, bilateral drainage is more physiologically sound than unilateral drainage. Various bilateral drainage techniques and SEMS that facilitate bilateral deployment are available . Nonetheless, multiple metal stenting for bilateral or multi‐sectoral drainage is still technically difficult.…”
Section: Bilateral (Multi‐sectoral) Drainagementioning
confidence: 99%
“…Also, bilateral drainage is more physiologically sound than unilateral drainage. Various bilateral drainage techniques and SEMS that facilitate bilateral deployment are available . Nonetheless, multiple metal stenting for bilateral or multi‐sectoral drainage is still technically difficult.…”
Section: Bilateral (Multi‐sectoral) Drainagementioning
confidence: 99%
“…It has recently been reported that combined simultaneous stent‐by‐stent (SBS) and stent‐in‐stent (SIS) method (SBSIS) can reduce the technical difficulty of tri‐sectoral metal stenting for high‐grade malignant hilar biliary obstruction (MHBO) 1–4 . However, inserting a third metal stent (MS) remains challenging 4 .…”
Section: Brief Explanationmentioning
confidence: 99%
“…It has recently been reported that combined simultaneous stent‐by‐stent (SBS) and stent‐in‐stent (SIS) method (SBSIS) can reduce the technical difficulty of tri‐sectoral metal stenting for high‐grade malignant hilar biliary obstruction (MHBO) 1–4 . However, inserting a third metal stent (MS) remains challenging 4 . More recently, simultaneous triple SBS placement using ultra‐thin delivery systems has helped avoid failures of the third MS insertion, but this technique cannot be performed for non‐large‐diameter common bile ducts 5 .…”
Section: Brief Explanationmentioning
confidence: 99%
“…Multiple stent deployments are often needed, and plastic stents (PS) or uncovered self‐expandable metal stents (SEMS) are commonly used. However, a recent study showed that the efficiency of the use of PS for HMBO was inferior to that of SEMS 1 . Additionally, the uncovered SEMS has the disadvantage of being non‐removable, precluding re‐interventions.…”
Section: Figurementioning
confidence: 99%